2021
DOI: 10.1159/000517473
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of a Single Multiallergen Subcutaneous Immunotherapy in Polyallergic Patients

Abstract: <b><i>Background:</i></b> As the number of allergic sensitizations increases the severity of allergic respiratory diseases worsens. Multiple monoallergen immunotherapy can be accompanied by poor treatment adherence and high costs, single multiallergen immunotherapy needs to prove efficacy whilst maintaining a good safety profile. <b><i>Methods:</i></b> Observational, retrospective, multicenter study using a 2-pollen single undiluted multiallergen subcutaneous imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These trials demonstrated significant improvement in patients who received mixtures of multiple, unrelated allergen extracts, but these studies were done prior to better standardization of extracts 2773–2776 . More recent studies based in Spain have also supported multi‐allergen immunotherapy 2777,2778 . A systematic review in 2009 evaluated 13 multi‐allergen immunotherapy studies (11 SCIT, one SLIT, and one both) and corroborated that co‐administration of two extracts is in fact clinically effective 2779 .…”
Section: Managementmentioning
confidence: 99%
“…These trials demonstrated significant improvement in patients who received mixtures of multiple, unrelated allergen extracts, but these studies were done prior to better standardization of extracts 2773–2776 . More recent studies based in Spain have also supported multi‐allergen immunotherapy 2777,2778 . A systematic review in 2009 evaluated 13 multi‐allergen immunotherapy studies (11 SCIT, one SLIT, and one both) and corroborated that co‐administration of two extracts is in fact clinically effective 2779 .…”
Section: Managementmentioning
confidence: 99%